Green Extraction of Cellulose Nanocrystals of Polymorph II from Cynara scolymus L.: Challenge for a “Zero Waste” Economy - Marianna Potenza; Laura Bergamonti; Pier Paolo Lottici; Lara Righi; Laura Lazzarini; Claudia Graiff (Crystals, 2022)
The increase of agri-food wastes by agriculture and industries is one of the main causes of environmental pollution. Here we propose the recycling of Cynara scolymus L. wastes to obtain polymorph II cellulose nanocrystals (CNC). Two different extraction procedures are compared: (i) Soxhlet extraction in an ethanol/toluene mixture, and (ii) water boiling of the agricultural waste. Both procedures were followed by purification of cellulose fibers through bleaching treatments and extraction of cellulose nanocrystals by acid hydrolysis. CNCs have been extensively characterized by FTIR spectroscopy, electrophoretic light scattering measurements, X-ray powder diffraction methods, transmission electron microscopy, and thermogravimetric analyses. Extracted CNC are rod-like-shaped polymorph IIs with a good crystallinity index, and they are characterized by high hydrogen bonding intensity. The ELS measurements on samples from both procedures show good results regarding the stability of the CNC II sol (ζ < −40 ± 5 mV), comparable to that of the CNC polymorph I. Both polymorph II CNCs show better thermal stability, compared to CNC I. The results show that the easy extraction procedure from agricultural Cynara scolymus L. waste can be used to produce high-quality cellulose nanocrystals as a green alternative to the commonly used synthetic route.